Cash Distribution Model with Safety Constraints - Guerrero, William J.; Sarmiento-Lepesqueur, Angélica; Martínez-Agaton, Cristian (Springer, 2020)
This article studies the cash distribution problem for bank correspondents that are geographically dispersed, and the associated risk indicators, service times, and logistics costs. The proposed model is a variant of the Inventory Routing Problem (IRP) that considers risk-management strategies. The model considers a single cash center with unlimited capacity, from which cash deliveries are carried out by a single vehicle with limited capacity for cash distribution. The bank correspondents to which the cash deliveries are made handles a limited storage capacity. This paper considers the routing decisions of vehicles with hard time window, and risk constraints focused on inducing unpredictability of routes in a cash supply chain. The proposed model is denoted as a risk constrained inventory routing problem with time Windows (RcIRPTW). A mathematical formulation based on mixed-integer programming is proposed, studying the impact of incidents risks in the transport of cash, generating computational experiments on test instances where four types of variations of the IRP are evaluated with several random demand scenarios. The results show the importance of simultaneously optimizing inventory decisions considering routing and inventory costs along with the consideration of risk mitigation strategies. These risk constraints force changing the routes of the vehicle, reducing incidents rates, and reducing route predictability for secure transportation and logistics.

Este artículo estudia el problema de la distribución de efectivo para los corresponsales bancarios geográficamente dispersos y los indicadores de riesgo, tiempos de servicio y costos logísticos asociados. El modelo propuesto es una variante del problema de enrutamiento de inventario (IRP) que considera estrategias de gestión de riesgos. El modelo considera un único centro de efectivo con capacidad ilimitada, desde el cual las entregas de efectivo se realizan en un único vehículo con capacidad limitada para la distribución de efectivo. Los corresponsales bancarios a los que se realizan las entregas de efectivo manejan una capacidad de almacenamiento limitada. Este documento considera las decisiones de ruta de los vehículos con una ventana de tiempo difícil y las restricciones de riesgo enfocadas en inducir la imprevisibilidad de las rutas en una cadena de suministro de efectivo. El modelo propuesto se denota como un problema de enrutamiento de inventario con restricciones de riesgo con ventanas de tiempo (RcIRPTW). Se propone una formulación matemática basada en programación de enteros mixtos, estudiando el impacto de los riesgos de incidentes en el transporte de efectivo, generando experimentos computacionales en instancias de prueba donde se evalúan cuatro tipos de variaciones del PIR con varios escenarios de demanda aleatorios. Los resultados muestran la importancia de optimizar simultáneamente las decisiones de inventario considerando los costos de enrutamiento e inventario junto con la consideración de estrategias de mitigación de riesgos. Estas limitaciones de riesgo obligan a cambiar las rutas del vehículo, reducir las tasas de incidentes y reducir la previsibilidad de la ruta para un transporte y una logística seguros.
Keywords: Cadena de suministro de moneda; Elección de transporte - Modelos matemáticos; Choice of transportation - Mathematical models; Problema de enrutamiento de vehículos; Vehicle routing problem; Logística empresarial; Business logistics; Cash distribution; Inventory routing; Time windows; Branch banking; Risk management; Currency supply chain